2021
DOI: 10.1093/joc/jqab034
|View full text |Cite
|
Sign up to set email alerts
|

The Distorting Prism of Social Media: How Self-Selection and Exposure to Incivility Fuel Online Comment Toxicity

Abstract: Though prior studies have analyzed the textual characteristics of online comments about politics, less is known about how selection into commenting behavior and exposure to other people’s comments changes the tone and content of political discourse. This article makes three contributions. First, we show that frequent commenters on Facebook are more likely to be interested in politics, to have more polarized opinions, and to use toxic language in comments in an elicitation task. Second, we find that people who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 65 publications
4
77
1
Order By: Relevance
“…Indeed, previous studies have found "significant spikes of abuse on particular days" (Ward and McLoughlin, 2020, p. 61; see also Su et al, 2018 for social media pages of news outlets), but also that incivility always seems to be prevalent on social media to a certain degree (Theocharis et al, 2020). As indicated above, research has also shown that incivility in the original post influences the amount of incivility in user comments (Gervais, 2017;Kim et al, 2021;Rega and Marchetti, 2021;Shmargad et al, 2021). This kind of "contagious incivility" has been associated with different mechanisms, with explanations ranging from behavioral mimicry to incivility increasing feelings of anger or changing social media users' perceived social norms (for an overview, see Kim et al, 2021).…”
Section: Post Characteristicsmentioning
confidence: 87%
See 4 more Smart Citations
“…Indeed, previous studies have found "significant spikes of abuse on particular days" (Ward and McLoughlin, 2020, p. 61; see also Su et al, 2018 for social media pages of news outlets), but also that incivility always seems to be prevalent on social media to a certain degree (Theocharis et al, 2020). As indicated above, research has also shown that incivility in the original post influences the amount of incivility in user comments (Gervais, 2017;Kim et al, 2021;Rega and Marchetti, 2021;Shmargad et al, 2021). This kind of "contagious incivility" has been associated with different mechanisms, with explanations ranging from behavioral mimicry to incivility increasing feelings of anger or changing social media users' perceived social norms (for an overview, see Kim et al, 2021).…”
Section: Post Characteristicsmentioning
confidence: 87%
“…As indicated above, research has also shown that incivility in the original post influences the amount of incivility in user comments (Gervais, 2017;Kim et al, 2021;Rega and Marchetti, 2021;Shmargad et al, 2021). This kind of "contagious incivility" has been associated with different mechanisms, with explanations ranging from behavioral mimicry to incivility increasing feelings of anger or changing social media users' perceived social norms (for an overview, see Kim et al, 2021). Interestingly, more incivil and emotionally charged comments also seem to attract more engagement on social media (Stieglitz and Dang-Xuan, 2013;Kim et al, 2021).…”
Section: Post Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations